Learning work ethic from the sunnah - Abd Rahman, Shukran (Human Assistance & Development International Inc. (HADI Inc.), 2025)
Work ethic refers to an individual's intrinsic values that regulate or govern his or her approach to work. It is shaped by purpose, sustained effort, and a belief system rooted in moral responsibility.